Palavra-paisagem: ecologia da palavra no Instagram de Lilia Schwarcz - Arruda, Juliana Gomide (2023)
This work aims to investigate the word in the hypermedia environment based on a phenomenological approach of Lilia Schwarcz’s profile on Instagram, in order to reflect on whether this word produces a cultural environment. For this purpose, the research is based on multiple categories of data, such as profile publications and user comments, information from social media analysis sites and Lilia Schwarcz interviews. Considering that today most words are provided by media mechanisms and that many of the communication processes take place on social media platforms, such as Instagram, we understand that it is necessary to look at the communication dynamics of this place. We will discuss the word on Instagram based on Aby Warburg’s universalizing concept of image - after all, every word is an image - to understand it as a media and a linking resource, capable of impacting and creating cultural environments. We will approach the word as a primary means of communication, a practice of the body, and given that this body is biological and cultural, we will deal with the word in dialogue with the environment. The research hypothesis is centered on the understanding that the use of an analytical and mostly written word in Lilia Schwarcz’s profile creates different reading components that build a cultural environment. As a result, we found that the word and the environment, involving the bodies mediated by machines, are connected and act together in the creation of this cultural environment around the word in Lilia Schwarcz’s profile. The theoretical foundation is essentially based on Aby Warburg, Boris Cyrulnik, Harry Pross, Norval Baitello Junior and Vilém Flusser